Unstressed Vocalism in the Pskov Dialects and Its Reflection in 17th-Century Private Correspondence of Ivangorod Merchants - Ryko, Anastasiia (Slavistica Vilnensis, 2026)
The article examines the reflection of unstressed vocalism, primarily akanye, in the private correspondence of Ivangorod merchants of the 17th century. The initial aim is to analyse written data in order to determine to what extent they allow conclusions to be drawn about the nature of unstressed vocalism in a regional dialect for which the relationship between akanye and okan’e in the 17th century remains a matter of scholarly debate. Particular attention is paid to distinguishing between orthographic and phonetically motivated spellings. It is shown that cases of letter substitution in the representation of unstressed vowels require cautious interpretation, since a substantial part of such spellings may be explained by orthographic tradition, lexicalization, or scribal errors. The distribution of spellings with a and o in pre-stressed and post-stressed positions does not provide sufficient grounds for reconstructing a system of strong akanye or a Gdov-type vocalism in the Ivangorod dialect of the period under consideration. At the same time, the reflection of the e > o shift in unstressed positions, a feature characteristic of okanye systems, makes it possible to assume the predominance of an okanye-based type of vocalism. Evidence from post-stressed syllables, although less conclusive, allows for the hypothesis of a weakening of unstressed vowel contrasts and a tendency towards their reduction.
Keywords: historical phonetics; unstressed vocalism; akanye; North Pskov dialects; 17th-century private correspondence; orthographic usage